2019
DOI: 10.3332/ecancer.2019.973
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence on first-line treatment for metastatic renal cell carcinoma with non-clear cell and sarcomatoid histologies: are sunitinib and pazopanib interchangeable?

Abstract: Introduction: Non-clear cell renal cell carcinoma (nccRCC) and sarcomatoid renal cell carcinoma (sRCC) are underrepresented in clinical trials. Treatment approaches are frequently extrapolated from data of clear cell renal cell carcinoma, in which pazopanib is non-inferior to sunitinib. We aim to compare the effectiveness of first-line sunitinib and pazopanib for nccRCC and sRCC. Methods: We evaluated a retrospective cohort of patients with metastatic nccRCC and sRCC treated with first-line sunitinib or pazopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[58][59][60]63 However, interestingly, in a retrospective cohort study of patients with metastatic nccRCC treated with pazopanib or sunitinib, pazopanib was associated with inferior OS. 64 Thus, while TKI monotherapy has shown some clinical efficacy in nccRCC subtypes, there is much room for improvement.…”
Section: Pazopanibmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60]63 However, interestingly, in a retrospective cohort study of patients with metastatic nccRCC treated with pazopanib or sunitinib, pazopanib was associated with inferior OS. 64 Thus, while TKI monotherapy has shown some clinical efficacy in nccRCC subtypes, there is much room for improvement.…”
Section: Pazopanibmentioning
confidence: 99%
“…The trials found pazopanib to be well tolerated overall; however, CTCAE grade 3 adverse events were reported in 20% to 55% of patients, the most common being fatigue, diarrhea and hypertension 58‐60,63 . However, interestingly, in a retrospective cohort study of patients with metastatic nccRCC treated with pazopanib or sunitinib, pazopanib was associated with inferior OS 64 . Thus, while TKI monotherapy has shown some clinical efficacy in nccRCC subtypes, there is much room for improvement.…”
Section: Treatmentmentioning
confidence: 99%